Evaluation of Environmental Sanitation in Laino Central Market Operations: Assessing Compliance with Health Standards in Raha City - Vifi Febriani; Ridwan Adi Surya; La Ode Ahmad Nur Ramadhan; La Ode Midi; Asramid Yasin; Wa Ode Hastiani Fahidu (Lembaga Pengembangan Kinerja Dosen, 2025)
Sanitation issues are critical and need to be addressed by all parties, as they are closely linked to public health. Sanitation refers to efforts aimed at preventing disease by eliminating or controlling environmental factors that contribute to disease transmission. One of the public service facilities that must organize proper sanitation is the public market. This study aims to evaluate the environmental sanitation of Sentral Laino Market in Raha City. The research utilizes a quantitative descriptive analysis method to assess various parameters of the market’s sanitation. A total of 14 parameters were measured based on the Regulation of the Indonesian Minister of Health No. 17 of 2020. The parameters and their respective values are as follows: Market Building (75%), Stall Building (63%), Waste Disposal (60%), Sewage and Drainage (57%), Toilets (88%), Clean Water (83%), Food and Foodstuff Sales Places (57%), Control of Disease Transmitting Animals (33%), Market Security (50%), Lighting, Temperature and Humidity (100%), Hand Washing Places (50%), Parking Places (75%), Traders/Employees (40%), and Visitors/Buyers (25%). Among the 14 components assessed, 5 components met the required standards, while 9 components did not meet the eligibility criteria. The overall category value, based on the “yes” answers from all the components, totaled 56 points (60%). According to the Regulation of the Indonesian Minister of Health No. 17 of 2020 concerning Healthy Markets, a market is considered eligible if the total score reaches ≥70%. Therefore, the Sentral Laino Market does not meet the standards for a healthy market. This study highlights the need for significant improvements in various aspects of the market’s sanitation to ensure public health and safety. It is crucial for local authorities and stakeholders to address these sanitation challenges to create a healthier environment for both traders and consumers.